2007
DOI: 10.1007/978-3-540-73321-8_52
|View full text |Cite
|
Sign up to set email alerts
|

Automatic, Body Measurements Based Generation of Individual Avatars Using Highly Adjustable Linear Transformation

Abstract: In this paper part of the work of the research project 'IntExMa' is presented, that aims at the development of an interactive, in-store sales support system focusing on the virtual 'try-on' of clothing. Customers are provided with highly realistic, individualized, three-dimensional virtual counterparts, derived from a small number of body measurements. The paper describes in detail the approach followed for the required automatic generation of avatars. It is based on a sophistication of the well-known concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Thus it is strongly recommended for manufacturers/industry to adopt this highly useful tool and achieve financial gains by reducing cost on account of building physical prototypes and testing with real human beings. Further manufacturing/ marketing firms can reach out to potential buyers using virtual technology as a training/demonstration tool [18] regarding how to use their products and also giving gender, somatotypes specific instructions if any (where ergonomic compromise is inevitable) enabling them to make well judged buying decisions [19] for satisfying error free use. However during this study, it was found impossible to create manikins representing children and elderly populations as desired by authors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is strongly recommended for manufacturers/industry to adopt this highly useful tool and achieve financial gains by reducing cost on account of building physical prototypes and testing with real human beings. Further manufacturing/ marketing firms can reach out to potential buyers using virtual technology as a training/demonstration tool [18] regarding how to use their products and also giving gender, somatotypes specific instructions if any (where ergonomic compromise is inevitable) enabling them to make well judged buying decisions [19] for satisfying error free use. However during this study, it was found impossible to create manikins representing children and elderly populations as desired by authors.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify anatomical site‐specific UV exposure with respect to the direct, diffuse, and reflected components, we developed SimUVEx v2 , a numerical tool based on 3D graphic techniques and human modeling to estimate the exposure of a 3D virtual mannequin. Human modeling that combines technology with science is widely implemented in various fields such as medical treatment , surgery , ergonomics , film and television , and sports . Although several studies have addressed the human body exposure to UV , to the best of our knowledge, very limited efforts have been brought to the application of human modeling and 3D computer graphics for estimating and visualizing UV exposure .…”
Section: Introductionmentioning
confidence: 99%
“…These topics range from the realistic modeling of humans-their looks, texture, and skin deformation-to the more advanced topics of behavior, motion prediction, and cognitive aspects." Human modeling and simulation is now a mature field [15] [22] [23] and apart from the film industry, it has been successfully applied in a wide range of areas: training [25] , ergonomics [21] [24] [27] , medicine [26] , surgery [28] and many more [30] . Surprisingly, although a particular interest has been dedicated to the human body exposure to UV [33] [34] , very limited efforts have been brought to the application of human modeling and 3D Computer Graphics for estimating and visualizing exposure to irradiation in general [29] and to UV irradiation in particular [12] .…”
Section: Introductionmentioning
confidence: 99%